Influence of dynamic training on the biomechanics and height of volleyball spike in young players - Nasrallah R Misjel; Ali Sh Jabbarb; Hussein M Tuama; Haidar Sh Jabbard (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.